The measurement set representation of the body posture based on group theory - Deng, Changjian; Xie, Xiaona (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The foundation of measurement is the representation of measurement set. The paper proposes a body posture measurement set representation method based on concepts of group, fields, and ring. It attempts to explore the intrinsic relationship among numerous different measurement set. The attitude sensor is used to measure the attitude, and the measurement set representation and processing are analyzed based on the lie group theory in the paper. In the paper, the paper maps body posture data into image, and it is easier to identify the error of posture measurement data. Meanwhile, the simulation and test results show that the method can represent body posture data and detect it’s defects easily.